Strategi Humas Dinas Perhubungan Kota Surabaya Dalam Mensosialisasikan Moda Transportasi Modern Di Kota Surabaya - Febian Ragil Prawesti; Ariyan Alfraita; Fitria Widiyani Roosinda (CV. ITTC INDONESIA, 2026)
Modern transportation is part of the efforts of the Surabaya City Government to realize an integrated transportation system and support the smart city concept, which requires an effective public communication strategy. This study aims to analyze the public relations strategy of the Surabaya City Transportation Agency in socializing modern transportation modes using a descriptive qualitative approach and the PESO Model theory (Paid, Earned, Shared, and Owned Media). The results indicate that the public relations communication strategy is considered fairly effective, as reflected in the increased public awareness and the growth in the number of passengers from year to year. In conclusion, although the socialization strategy has been implemented well, there is still a need to strengthen media integration and expand non-digital communication channels so that information about modern transportation can reach all segments of society more evenly.